2019
DOI: 10.3892/or.2019.7104
|View full text |Cite
|
Sign up to set email alerts
|

JS‑K induces G2/M phase cell cycle arrest and apoptosis in A549 and H460 cells via the p53/p21WAF1/CIP1 and p27KIP1 pathways

Abstract: Lung cancer is one of the most common malignancies worldwide, with high mortality and morbidity rates. O2-(2,4-dinitrophenyl)-1-[(4-ethoxycarbonyl)piperazin-1-yl]diazen-1-ium-1,2-diolate (JS-K) is a potent anticancer agent that acts against a subset of human non-small cell lung cancer (NSCLC) cell lines; however, the underlying mechanisms of JS-K in NSCLC remain unclear. The present study aimed to evaluate the anticancer effect of JS-K and investigate its underlying mechanisms in A549 and H460 cells. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In addition, cell % was markedly reduced from 88.79% to 31.22% at G0/G1 phase when A549 cells were treated with C8. Obtained results suggested that C8 demonstrated a significant antineoplastic effect and led to the stoppage A549 cell cycle progression at G2/M, metaphase, after the gestation period of 24 h. These results were in accordance with the other recent research conducted on A549 cells, wherein the anticancer effects were attributed to the blocking of the G2/M phase [54][55][56].…”
Section: Cell Cycle Analysissupporting
confidence: 89%
“…In addition, cell % was markedly reduced from 88.79% to 31.22% at G0/G1 phase when A549 cells were treated with C8. Obtained results suggested that C8 demonstrated a significant antineoplastic effect and led to the stoppage A549 cell cycle progression at G2/M, metaphase, after the gestation period of 24 h. These results were in accordance with the other recent research conducted on A549 cells, wherein the anticancer effects were attributed to the blocking of the G2/M phase [54][55][56].…”
Section: Cell Cycle Analysissupporting
confidence: 89%
“…Western blot analysis showed that p21 and p27 expression was significantly increased after o-GQD administration, which was consistent with the results from the apoptosis protein array. p21 and p27 affect the cell cycle by regulating the expression of CDKs and cyclin [ 19 ], and previous studies also indicated that the increase of p21 and p21 protein expression promotes G2/M cell cycle arrest [ 21 , 22 ]. Our results also revealed that o-GQD treatment down-regulated cyclin D1 and cyclin B1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that there are some differences in response to this compound between vascular SMCs and cancer cells. In cancer cells, CFI-400945 treatment upregulated the expression of p53, an essential regulator of the G2/M checkpoint [ 32 , 33 ], which activates cell cycle inhibitors, including p21 and p27 [ 34 ], and arrests the cell cycle. Our study revealed that CFI-400945 increased p27 protein levels but decreased p21 expression, suggesting that CFI-400945 treatment caused SMC cell cycle arrest mainly through the p53/p27 pathway.…”
Section: Discussionmentioning
confidence: 99%